ANALISIS TINGKAT KUALITAS WEBSITE CROWDFUNDING KITABISA.COM TERHADAP PENGGALANGAN DANA COVID-19 MENGGUNAKAN METODE E-S-QUAL DAN WEBQUAL 4.0 - Siti Khofifah (2021)
Kitabisa.com is a company engaged in fundraising and donations by utilizing websites and mobile applications for individuals, organizations, communities and companies that want to raise funds by making online donations for various social personal, creative and other purposes. During the Covid - 19 pandemic, which was a worldwide virus outbreak which resulted in many shortages both in terms of goods and finances as well as the economic crisis that hit Indonesia that made people work together to make donations online on the kitabisa.com platform. The number of users of the website kitabisa.com currently does not guarantee the level of user trust in this website.The level of wesite quality become a factor that must be considered in a website crowdfunding. Therefore we need a website analysis using the E-S-Qual method and Webqual 4.0 method. Data collection technique used a questionnaire and obtained 203 respondents. Data processing in this study using Smartpls 3.0. The test results of the seven hypotheses, there were 3 rejected hypotheses, namely privacy, compensation, and contact. The results of his research that the level of quality of the website has a significant effect on user satisfaction in making donations to Kitabisa.com. This is evident from the rsquare value of 0.574. These results indicate that 57.4% user satisfaction level of website quality significantly affects user satisfaction in making donations on Kitabisa.com, and recommendations for improving the quality of the Kitabisa.com website.